2020
DOI: 10.3390/cryst10040250
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Chemistry and Luminescence Properties of Eu-Doped Polycrystalline Hydroxyapatite Synthesized by Chemical Precipitation at Room Temperature

Abstract: Europium-doped hydroxyapatite Ca10(PO4)6(OH)2 (3% mol) powders were synthesized by an optimized chemical precipitation method at 25 °C, followed by drying at 120 °C and calcination at 450 °C and 900 °C. The obtained nanosized crystallite samples were investigated by means of a combination of inductively coupled plasma (ICP) spectroscopy, powder X-ray diffraction (PXRD), Fourier Transform Infrared (FTIR), Raman and photoluminescence (PL) spectroscopies. The Rietveld refinement in the hexagonal P63/m space group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…TPCs are biomaterial particularly wanted for their biocompatibility in human biosystem [1], and for the possibility of different cation replacements at the sites typically occupied by Ca [11], giving rise to different products, employed as commercial cement and paste for bone replacement [13,14]. In this regard, they are preferred to the more common synthetic Ca 10 (PO 4 ) 6 (OH) 2 hydroxyapatite because of their brittle nature [15,16]. Recently, additional interest has been also devoted to a series of rare-earth-doped TCP that are largely investigated as possible optical materials for biosciences application [10,11,17].…”
Section: Introductionmentioning
confidence: 99%
“…TPCs are biomaterial particularly wanted for their biocompatibility in human biosystem [1], and for the possibility of different cation replacements at the sites typically occupied by Ca [11], giving rise to different products, employed as commercial cement and paste for bone replacement [13,14]. In this regard, they are preferred to the more common synthetic Ca 10 (PO 4 ) 6 (OH) 2 hydroxyapatite because of their brittle nature [15,16]. Recently, additional interest has been also devoted to a series of rare-earth-doped TCP that are largely investigated as possible optical materials for biosciences application [10,11,17].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, samples prepared by hydrothermal treatment exhibit a nanorod-like morphology that enhances luminescence due to the high packing density and reduction of light scattering [ 61 ]. Working at low temperatures, such as 120 °C, led to the ordering of Eu 3+ ions at the Ca 1 site [ 62 ]. Silva et al observed that the thermal treatment of the doped NPs from 500 °C to 800 °C induces the diffusion of the rare element from Ca 1 to Ca 2 sites that seem to be more energetically stable to Eu 3+ [ 63 ].…”
Section: Impact Of Lanthanide Incorporation On the Morphology And Pro...mentioning
confidence: 99%
“…Its chemical formula is Ca 10 (PO 4 ) 6 (OH) 2 . The Ca/P ratio in stoichiometric hydroxyapatite is equal to 1.67, but in nonstoichiometric hydroxyapatite it is between 1.5–2.0 [ 2 ]. The compound is a part of human bones and teeth, which makes them properly durable.…”
Section: Introductionmentioning
confidence: 99%